THE EFFECTIVENESS OF ZINC AND RISEDRONATE ON BONE TURNOVER IN RAT MODEL OF OSTEOPOROSIS ASSESSED WITH THE EXPRESSION OF β-CROSSLAPS - Adam Fajar; Mohammad Rizal Chaidir; Dicky Mulyadi; Ahmad Ramdan; Yoyos Dias Ismiarto (Journal Orthopaedi and Traumatology Surabaya)
Background: Osteoporosis prevalence in Indonesia is high. Risedronate commonly used for treating the osteoporosis. Unfortunately, long term therapy can cause hazardous adverse effect to the patient. Previous research in rat model osteoporosis, Zinc have a potential effect to prevent and rebuild bone structure with osteoblast stimulation in bone formation and osteoclast activity inhibition in bone resorption by increasing Osteoprotegerin production, that inhibit bond between RANKL and RANK.